A rapid synthesis of the evidence on interventions supporting self-management for people with long-term conditions: PRISMS - Practical systematic RevIew of Self-Management Support for long-term conditions - Stephanie JC Taylor; Hilary Pinnock; Eleni Epiphaniou; Gemma Pearce; Hannah L Parke; Anna Schwappach; Neetha Purushotham; Sadhana Jacob; Chris J Griffiths; Trisha Greenhalgh; Aziz Sheikh (National Institute for Health Research, 2014)
Background: Despite robust evidence concerning self-management for some long-term conditions (LTCs), others lack research explicitly on self-management and, consequently, some patient groups may be overlooked. Aim: To undertake a rapid, systematic overview of the evidence on self-management support for LTCs to inform health-care commissioners and providers about what works, for whom, and in what contexts. Methods: Self-management is 'the tasks . . . individuals must undertake to live with one or more chronic conditions . . . [including] . . . having the confidence to deal with medical management, role management and emotional management of their conditions'. We convened an expert workshop and identified characteristics of LTCs potentially of relevance to self-management and 14 diverse exemplar LTCs (stroke, asthma, type 2 diabetes mellitus, depression, chronic obstructive pulmonary disease, chronic kidney disease, dementia, epilepsy, hypertension, inflammatory arthropathies, irritable bowel syndrome, low back pain, progressive neurological disorders and type 1 diabetes mellitus). For each LTC we conducted systematic overviews of systematic reviews of randomised controlled trials (RCTs) of self-management support interventions ('quantitative meta-reviews'); and systematic overviews of systematic reviews of qualitative studies of patients' experiences relating to self-management ('qualitative meta-reviews'). We also conducted an original systematic review of implementation studies of self-management support in the LTCs. We synthesised all our data considering the different characteristics of LTCs. In parallel, we developed a taxonomy of the potential components of self-management support. Results: We included 30 qualitative systematic reviews (including 515 unique studies), 102 quantitative systematic reviews (including 969 RCTs), and 61 studies in the implementation systematic review. Effective self-management support interventions are multifaceted, should be tailored to the individual, their culture and beliefs, a specific LTC and position on the disease trajectory, and underpinned by a collaborative/communicative relationship between the patient and health-care professional (HCP) within the context of a health-care organisation that actively promotes self-management. Self-management support is a complex intervention and although many components were described and trialled in the studies no single component stood out as more important than any other. Core components include (1) provision of education about the LTC, recognising the importance of understanding patients' pre-existing knowledge and beliefs about their LTC; (2) psychological strategies to support adjustment to life with a LTC; (3) strategies specifically to support adherence to treatments; (4) practical support tailored to the specific LTC, including support around activities of daily living for disabling conditions, action plans in conditions subject to marked exacerbations, intensive disease-specific training to enable self-management of specific clinical tasks; and (5) social support as appropriate. Implementation requires a whole-systems approach which intervenes at the level of the patient, the HCP and the organisation. The health-care organisation is responsible for providing the means (both training and time/material resources) to enable HCPs to implement, and patients to benefit from, self-management support, regularly evaluating self-management processes and clinical outcomes. More widely there is a societal need to address public understanding of LTCs. The lack of public story for many conditions impacted on patient help-seeking behaviour and public perceptions of need. Conclusions: Supporting self-management is inseparable from the high-quality care for LTCs. Commissioners and health-care providers should promote a culture of actively supporting self-management as a normal, expected, monitored and rewarded aspect of care. Further research is needed to understand how health service managers and staff can achieve this culture change in their health-care organisations. Study registration: This study is registered as PROSPERO CRD42012002898. Funding: The National Institute for Health Research Health Services and Delivery Research programme.